Experimental analysis of multistatic multiband radar signatures of wind turbines - Balleri, Alessio; Fioranelli, Francesco; Ritchie, Matthew; Griffiths, Hugh D. (Institution of Engineering and Technology (IET), 2016)
This study presents the analysis of recent experimental data acquired using two radar systems at S-band and X-band to measure simultaneous monostatic and bistatic signatures of operational wind turbines near Shrivenham, UK. Bistatic and multistatic radars are a potential approach to mitigate the adverse effects of wind farm clutter on the performance of radar systems, which is a well-known problem for air traffic control and air defence radar. This analysis compares the simultaneous monostatic and bistatic micro-Doppler signatures of two operational turbines and investigates the key differences at bistatic angles up to 23°. The variations of the signature with different polarisations, namely vertical transmitted and vertical received and horizontal transmitted and horizontal received, are also discussed.
Keywords: Radar; Wind turbines; Micro-Doppler signatures